Artificial Intelligence, Transhumanism and Biopolitics: Theoretical Frameworks in the Past Two Decades - Popović, Miroslav M.; Kulenović, Nina (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2024)
Artificial Intelligence, Transhumanism and Biopolitics: Theoretical Frameworks in the Past Two Decades The subject of artificial intelligence has its roots in the 1920s, in the context of philosophy, literature, film, science and its popularization, and gained importance during the Second World War and is linked to the personality of the famous Alan Turing, his thoughts on smart machines, on the one hand, and the beginnings of the use of artificial intelligence for war purposes, on the other. AI has long been the subject of research in anthropology and other social sciences, as it permeates all spheres of social life and concerns philosophical and ethical issues, issues of political power structures and governance. The development of artificial intelligence has opened up space for eternal consideration of the construction of the future of humanity and the role of man and machines in it. The issue of AI development has long occupied science fiction writers and filmmakers, and with the growing popularity of this genre and the increasing reliance of ordinary people on digital technologies in everyday life, the interest for this issue has also expanded to the population around the world. Researchers from the sphere of social sciences can, by their active engagement, try to interpret this phenomenon in an effort to provide a multitude of possible visions of the future of humanity, to point out the advantages, disadvantages and dangers related to access to modern technology, which is increasingly based on artificial intelligence, to show how humanity lives with it and how it affects the formation of new value systems and transforms human personality. In a way, AI can be considered, especially from the point of view of the wider population and certain scientists, among them anthropologists, as an opportunity to realize the utopian dream of objectivity of results and methods in a broader sense, devoid of the influence of politics, ideology and power structures. AI can serve as a tool to break free from the control of political and economic power centers. Also, according to some scientists, AI can ensure privacy and gradually lead to the transformation of existing models of political and economic order. On the other hand, some authors put transhumanism and the ideas it advocates under scrutiny precisely because it opens up the possibility of using AI as a means of biopolitics. For some, AI can become a means of global control or represents the realization of the fear that autonomous technology will one day deal with humanity. We see such apprehension as a motif in literature and film. Also, religious people and those with a somewhat more traditional value system believe that the development of technology and man’s increasing attachment to it, and inadequate attitude towards it, lead to alienation, changes in relations between people and the collapse of value systems, which in a long historical period were considered "desirable" and on which the survival of human society as we know it is based. Therefore, fear of the unknown dominates among these people and the anxiety that if too much freedom is allowed in the process of constantly overcoming previously set civilizational and technological boundaries, the existence and role of man in the modern world may become meaningless. The development of AI certainly leads to transformations of human society and the individual in it. They can be fast, undesirable, and sometimes society cannot keep pace with such transformations. On the other hand, they can contribute to progress in the sphere of science, health, education, economic and infrastructural development, help in solving population crises, enable the extension and facilitation of human life, etc. Given the multitude of possible scenarios when it comes to the question of directions in which the development of AI can lead humanity, only time will tell to which destination this development will take us.